MENGENAL ANALISIS DATA MELALUI PENDEKATAN FENOMENOLOGI - S, Laurensius Arliman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Data analysis is a crucial element in various fields of knowledge, including social sciences and humanities. The phenomenological approach in data analysis focuses on understanding subjective experiences and individual perceptions of specific phenomena. This research aims to explore and understand how the phenomenological approach is used in data analysis and its implications for research outcomes. This study employs a descriptive library research method, involving the collection and analysis of data from various relevant literature. The sources analyzed include books, journal articles, and other academic publications discussing the phenomenological approach in data analysis. This approach allows researchers to gain a comprehensive understanding of the concepts and applications of phenomenology in the context of data analysis. The findings indicate that the phenomenological approach provides deep insights into individual experiences and perceptions, enriching data analysis in qualitative research. By understanding subjective experiences, researchers can interpret data more profoundly and meaningfully. This study recommends the broader application of the phenomenological approach in data analysis to enhance the quality and relevance of research outcomes.